2002
DOI: 10.1152/ajpcell.00291.2001
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of ClC-2 chloride channel in rat and human epithelial tissues

Abstract: The ubiquitous ClC-2 Cl(-) channel is thought to contribute to epithelial Cl(-) secretion, but the distribution of the ClC-2 protein in human epithelia has not been investigated. We have studied the distribution of ClC-2 in adult human and rat intestine and airways by immunoblotting and confocal microscopy. In the rat, ClC-2 was present in the lateral membranes of villus enterocytes and was predominant at the basolateral membranes of luminal colon enterocytes. The expression pattern of ClC-2 in the human intes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
2
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 59 publications
7
93
2
2
Order By: Relevance
“…An apical localization and function in fluid secretion is also postulated for ClC-2 in lung epithelium (Blaisdell et al, 2000). In contrast with these results, we and others have shown ClC-2 transcript in surface epithelium of guinea pig distal colon, identified a basolateral membrane localization of ClC-2 in surface epithelium and demonstrated a functional Cl -conductance with rectification and selectivity properties consistent with this subcellular distribution of ClC-2 (Catalán et al, 2002;Lipecka et al, 2002;Catalán et al, 2004). ClC-2 knockout mouse models present blindness and male infertility and, it has been argued, transepithelial transport defects could be responsible for these alterations (Bösl et al, 2001;Nehrke et al, 2002).…”
Section: Introductioncontrasting
confidence: 57%
See 2 more Smart Citations
“…An apical localization and function in fluid secretion is also postulated for ClC-2 in lung epithelium (Blaisdell et al, 2000). In contrast with these results, we and others have shown ClC-2 transcript in surface epithelium of guinea pig distal colon, identified a basolateral membrane localization of ClC-2 in surface epithelium and demonstrated a functional Cl -conductance with rectification and selectivity properties consistent with this subcellular distribution of ClC-2 (Catalán et al, 2002;Lipecka et al, 2002;Catalán et al, 2004). ClC-2 knockout mouse models present blindness and male infertility and, it has been argued, transepithelial transport defects could be responsible for these alterations (Bösl et al, 2001;Nehrke et al, 2002).…”
Section: Introductioncontrasting
confidence: 57%
“…In the last two studies ClC-2 was co-localized with the tight junctions, where it was speculated to mediate Cl -efflux into the lumen. More recent experiments, however, report expression of ClC-2 at the basolateral membranes of surface colonic and small intestinal cells (Lipecka et al, 2002; Catalán -channel based on a high resolution X-ray diffraction study of a ClC from Salmonella typhimurium (Dutzler et al, 2003). The extracellular side is up.…”
Section: Cftr Is a Camp-activated CLmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, several studies suggested that ClC-2 may be present in apical membranes of lung (18) and intestinal (19,33) epithelia, although others obtained conflicting results (34,35). Finally, the testicular and retinal degeneration observed in Clcn2 Ϫ/Ϫ mice was suggested to result from a defect in transepithelial transport across the Sertoli cell and retinal pigment epithelium, respectively (24).…”
Section: Discussionmentioning
confidence: 99%
“…Sample preparation protocols are described in detail elsewhere 12,13 . Briefly, cells were washed on ice twice with phosphate-buffered saline (PBS) solution containing 0.1mM CaCl 2 and 1mM MgCl 2 .…”
Section: Cell Culturementioning
confidence: 99%